If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + 7 = 4x + 5 Reorder the terms: 3(-4 + x) + 7 = 4x + 5 (-4 * 3 + x * 3) + 7 = 4x + 5 (-12 + 3x) + 7 = 4x + 5 Reorder the terms: -12 + 7 + 3x = 4x + 5 Combine like terms: -12 + 7 = -5 -5 + 3x = 4x + 5 Reorder the terms: -5 + 3x = 5 + 4x Solving -5 + 3x = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 3x + -4x = 5 + 4x + -4x Combine like terms: 3x + -4x = -1x -5 + -1x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + -1x = 5 + 0 -5 + -1x = 5 Add '5' to each side of the equation. -5 + 5 + -1x = 5 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 5 + 5 -1x = 5 + 5 Combine like terms: 5 + 5 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 8x-37=2x+35 | | 6(y+38)-19=43 | | 3x+32=2x+26 | | 5(3x+2y)= | | 15025=45.5t^2+6100 | | -36-6x=7x+2x | | 10n^2-6=994 | | 5(7x+5)whenx=10solve | | 85=(x)(4x-3) | | 10n^2=994 | | N^2+9n+15=7 | | (x+5)+(2x+15)+(2x+10)=90 | | 5(2x-2)=3x+11 | | x(4x+13)=-3 | | x+(X*.10)=1280418 | | 5x+2x^2+2=0 | | h(t)=-4.9t^2+32+2 | | 4x-15+3x=5+7x-19 | | -4p+11-(-5p)-2= | | 36x^2-36x-216=0 | | 400+50x=4000 | | -81=-4+7(6b-5) | | y+4=0.5x+1 | | -7y+12+2y-1= | | 6(x+3)-8x=36 | | 4(8k+5)= | | (3x-5)(2x+8)= | | (x+3)(x+3)=X^2+81 | | 456=(20+2x)(15+2x) | | 1+4(x-8)=4-5(x-1) | | x^2+y^2-6x+4y+6=0 | | 8n+14=2n-4 |